Analysis of satisfaction, motivation and behavior in a federal public institution of higher education - Moreira, Sarah Tiburtino; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2020)
In federal public institution motivation and satisfaction of public servants is one of the factors responsible for the performance and commitment of these civil servants, being factors of great relevance in the results achieved by the institution. Thus, this research proposed to identify and analyze the main factors that influence the level of satisfaction in the technical-administrative work environment within a Federal Public Education Institution. The place defined for this research to take place was the Federal University of Espírito Santo (Ufes), at the São Mateus Campus, where the Centro Universitário Norte do Espírito Santo (Ceunes) is located. The technique chosen to conduct the data collection was a questionnaire, applied to technical-administrative servers, with closed and open questions. Accordingly, it was found that the main factors that influence levels of satisfaction are motivational factors, that is, those that are linked to their own function, and provide satisfaction. The following stand out: growth achieved, future perspectives, responsibility, recognition, professional and personal fulfillment. Therefore, this study contributed to demonstrate that human resources management policies at Ceunes need to be strengthened, in order to improve levels of server satisfaction with motivational factors, through efficient communication, training, recognition, among other factors. With the adoption of measures that enhance Ceunes’ staff , it is expected to obtain better results in the future.